A Dialogue about Social Weaving: The Weaving Kiosk and Weaving Lab. (3rd April 2021) - Hemmings, Jessica; Clausen, Rosa Tolnov; Fairbanks, Marianne
Abstract: Adopting the format of an edited and annotated conversation, Danish researcher and designer Rosa Tolnov Clausen, American artist and professor Marianne Fairbanks and British writer and professor Jessica Hemmings discuss some of the circumstances in which community hand weaving projects may flourish. Decisions around the types of space Clausen's Weaving Kiosk (2017–ongoing) and Fairbanks's Weaving Lab (2016–ongoing) have occupied, how hand weaving may be made portable, the impact of duration and responsibility toward the material, as well as social, outcomes are discussed. While our conversation tries to understand what is shared by the Kiosk and Lab, we also acknowledge where different cultural and historical contexts cause the potential and challenges of these two initiatives to differ. The Weaving Kiosk and Weaving Lab are not intended as performances, but instead place emphasis on how hand weaving may build social connections. The format of this article foregrounds the conversational nature of social hand weaving and hopefully offers inspiration to others interested in expanding the purpose of contemporary hand weaving and textile scholarship.